Mewujudkan Science Is Fun di SD melalui Sebuah Model Pembelajaran dalam Pendidikan Tinggi Jarak Jauh - A. A. Ketut Budiastra (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: This objective of the study was to share experience on how to make science interesting for elementary school students through preparing elementary school teachers by using TDPSPM strategy at distance education mode. Instructional media used were video recorded modeling which consists of an example the way teachers teach science in elementary school besides modules by implementing R & D cycles. Based on the data analyses of pretest and posttest it can be concluded that student’s achievement increased significantly. Further more, instruction’s strategy used by teachers which is put students as a center of instruction can bring into reality “science is fun” in elementary school.